Motivasi Keputusan Mahasiswa untuk Bekerja Sebagai Ojek Muslimah - Fuji Lestari; Muhammad Agus Saputra; Mutia Mutmainah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The phenomenon of increasing participation of female students in sharia-based transportation services such as Ojek Muslimah Universitas Riau (OMU) shows a change in work preferences among young Muslim women. This study aims to investigate the motivations and experiences of female students who choose to work as drivers in the community. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews with the founder of Ojek Muslimah Universitas Riau and one of the active drivers. The results of the study revealed that the main reasons for female students to join were economic needs, the desire to be independent, and the belief in a safe, flexible, and Islamic work system. Security factors, a women-only work environment, and Islamic dress and interaction rules are the main attractions. In addition, the existence of a supportive community also strengthens the enthusiasm and professionalism of the drivers. Despite facing challenges in terms of time management and social perception, female students are still able to carry out dual roles as students and workers. These findings indicate that part-time work based on religious values can be a relevant and meaningful alternative for Muslim women in meeting economic needs while maintaining their Islamic identity. This study recommends strengthening institutional support and the sustainability of similar work models in other campus environments.